2004
DOI: 10.1080/03014460410001663416
|View full text |Cite
|
Sign up to set email alerts
|

Body dimensions, exercise capacity and physical activity level of adolescent Nandi boys in western Kenya

Abstract: The aim of this study was to characterize untrained Nandi boys (mean age 16.6 years) from a town (n = 11) and from a rural area (n = 19) in western Kenya (altitude approximately 2000 m.a.s.l.) in regard to their body dimensions, oxygen uptake and physical activity level. The town boys had a mean maximal oxygen uptake (VO(2 max)) of 50 (range: 45-60) mL kg(-1) min(-1), whereas the village boys reached a value of 55 (37-63) mL kg(-1) min(-1) ( p<0.01) in VO(2 max). The running economy, determined as the oxygen c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
69
4
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(86 citation statements)
references
References 23 publications
9
69
4
4
Order By: Relevance
“…As in previous studies, a relationship was found M. N. Scholz and others between running economy and foot length (Anderson, 1996) and between running economy and BMI or lower-leg volume/moment of inertia (Anderson, 1996;Larsen et al, 2004). However, we showed that these relationships were no longer significant after correcting each variable (i.e.…”
Section: Discussionsupporting
confidence: 69%
“…As in previous studies, a relationship was found M. N. Scholz and others between running economy and foot length (Anderson, 1996) and between running economy and BMI or lower-leg volume/moment of inertia (Anderson, 1996;Larsen et al, 2004). However, we showed that these relationships were no longer significant after correcting each variable (i.e.…”
Section: Discussionsupporting
confidence: 69%
“…Previous studies 24,25 demonstrated a similar pattern of lower VO 2max among the more sedentary individuals. It appears that it is only with regular exercise regimes that university-attending individuals may attain a minimum-for-age VO 2max , as has previously been suggested 18 . It also appears that VO 2max is a more complete indicator of the fitness differences among subjects given that HR was affected by individuals dropping from the SRT at different levels, and the BP measures did not yield strict statistical differences.…”
Section: Discussionmentioning
confidence: 57%
“…Similarly aged male who exercised regularly attained VO 2max of 62 (58-71) ml/kg/min whereas runners in active training had VO 2max values of up to 68±1.4 ml/kg/min. 17 Another study comparing town and village dwellers 18 showed males of mean age 16.6 years from town setting attaining a mean VO 2max of 50 (45-60) ml/ kg/min whereas their village counterparts attained 55 (37-63) ml/kg/min (p<0.01).…”
Section: Introductionmentioning
confidence: 99%
“…Sin embargo, un estudio de Favier, Spielvogel, Desplanches, Ferretti, Kayser y Hoppeler (1995) reveló que no mejoraban mucho su VO₂ máx cuando se les estudiaba a nivel del mar. Aunque pueda haber una pequeña diferencia se debe considerar que la masa corporal de los chicos Nandi era solo 54 kg de media (Larsen et al, 2004), que es 12 kg de media menos que los chicos de origen caucásico (Andersen, 1994). Si el VO₂ máx es normalizado con el exponente 0,75, los chicos kenianos tendrán un VO₂ máx menor que el de los chicos de origen caucásico.…”
Section: Consumo Máximo De Oxígeno (Vo₂ Máx)unclassified
“…Por ello, los corredores kenianos de larga distancia de élite son más delgados que los corredores de élite escandinavos (Saltin et al, 1995b). Además, un estudio de chicos kenianos desentrenados demostró que no solo tenían una masa corporal más baja, sino que su masa corporal era mucho menor que la de la mayoría de los chicos de su edad de otros continentes (Larsen et al, 2004). Este estudió también indicó que la circunferencia de la pantorrilla de los chicos kenianos era menor que la de los chicos escandinavos.…”
Section: Factores Biomecánicos Y Economía De Carreraunclassified